Harmonisasi Beribadah Warga Muhammadiyah dan Nahdlatul Ulama di Mesjid At-Tawwabin Kelurahan Tobat Kota Padangsidimpuan - Syulhennisari Siregar; Dedy Suhendra (ARISTO, 2021)
Muhammadiyah and Nahdlatul Ulama are the two largest Islamic organizations in Indonesia which have several different understandings in the implementation of worship, so people assume that the harmonization of worship between followers of these two organizations is very difficult to carry out, but it is different with Muhammadiyah and Nahdlatul Ulama members who become worshipers in At-Tawwabin Mosque, worshipers in this mosque worship together, without any debate or dispute. The purpose of this research is to find out how the harmony of worship of Muhammadiyah and Nahdlatul Ulama residents in the mosque, and what factors influence the harmonization of worship. This research is expected to be beneficial for Muhammadiyah and Nahdlatul Ulama residents in maintaining harmony in worship of fellow Muslims and can be used as a reference to avoid conflicts between Islamic religious organizations in Indonesia. The research method used is a descriptive research method with a qualitative analysis approach, through a series of observations, interviews, and taking documentation, while the research location is in the District of Tobat, Padangsidimpuan City. The results of this study conclude that the form of harmonization is as in the implementation of fard prayers, Friday prayers, Tarwih prayers, holiday prayers, and the implementation of corpse prayers. While the factors that influence it are historical factors, family / kinship factors, the influence of Dalihan Na Tolu, government support, and blind fanatic attitudes of Muhammadiyah and NU residents in the mosque.